Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Ask your questions and receive precise answers from experienced professionals across different disciplines. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
: Let y = f(x) = x^1/3
Then dy = 1/3*x^(−2/3) dx
Since f(64) = 4.
We take x = 64 and dx = ∆x = 1
This gives dy = 1/3*(64)^(−2/3)* (1) = 1/48
∴65^(1/3) = f(64 + 1) ≈ f(64) + dy = 4 + 1/48 ≈ 4.021
Then dy = 1/3*x^(−2/3) dx
Since f(64) = 4.
We take x = 64 and dx = ∆x = 1
This gives dy = 1/3*(64)^(−2/3)* (1) = 1/48
∴65^(1/3) = f(64 + 1) ≈ f(64) + dy = 4 + 1/48 ≈ 4.021
Answer:
: Let y = f(x) = x^1/3
Then dy = 1/3*x^(−2/3) dx
Since f(64) = 4.
We take x = 64 and dx = ∆x = 1
This gives dy = 1/3*(64)^(−2/3)* (1) = 1/48
∴65^(1/3) = f(64 + 1) ≈ f(64) + dy = 4 + 1/48 ≈ 4.021
Read more on Brainly.com - https://brainly.com/question/19668#readmore
Step-by-step explanation:
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.